Effects of Kenaf (Hibiscus Cannabinus) as a Substitative Feed on Lactating Dairy Cattle - Chantiratikul, Anut (2005)
Improvement of ruminant feeding system by using locally grown fodder has received much attention in the tropics. Recently, kenaf has been shown to be a valuable fodder for beef cattle and small ruminants, but information on its use for dairy cow is scanty. Hence, the overall objective of the thesis was to examine the potential of using kenaf as a substitute for alfalfa hay (AH) and soybean meal (SBM) in dairy cow rations. Three experiments were carried out to achieve the above objective.